2008
DOI: 10.1007/s00330-008-0956-3
|View full text |Cite
|
Sign up to set email alerts
|

Measurement and determinants of infrarenal aortic thrombus volume

Abstract: Intra-luminal thrombus has been suggested to play a role in the progression of abdominal aortic aneurysm (AAA). The aims of this study were twofold. Firstly, to assess the reproducibility of a computer tomography (CT)-based technique for measurement of aortic thrombus volume. Secondly, to examine the determinants of infrarenal aortic thrombus volume in a cohort of patients with aortic dilatation. A consecutive series of 75 patients assessed by CT angiography with maximum aortic diameter > or = 25 mm were recru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
38
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 55 publications
(43 citation statements)
references
References 34 publications
4
38
1
Order By: Relevance
“…As previously reported, we confirmed an association between AAA diameter and the volume of the intra-aneurysmal thrombus [33][35]. The role of the intra-aneurysmal thrombus for AAA progression, however, is still controversial: several studies demonstrated that the size of an intra-aneurysmal thrombus is related to AAA progression and/or rupture [12], [36][38].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…As previously reported, we confirmed an association between AAA diameter and the volume of the intra-aneurysmal thrombus [33][35]. The role of the intra-aneurysmal thrombus for AAA progression, however, is still controversial: several studies demonstrated that the size of an intra-aneurysmal thrombus is related to AAA progression and/or rupture [12], [36][38].…”
Section: Discussionsupporting
confidence: 90%
“…This finding is in line with others showing that a thrombus may even reduce shear-stress imposed on the AAA wall [39][41]. In summary, the factors determining whether an intra-aneurysmal thrombus increases the risk for AAA progression or protects against deterioration of the disease are still unknown [35].…”
Section: Discussionsupporting
confidence: 88%
“…A recent study demonstrated a close correlation between thrombus volume and both total aortic volume (r=0.87, p <0.0001) and maximum AAA diameter (r=0.74, p <0.0001) 72. This was in keeping with previous smaller studies which quantified AAA thrombus 73,74.…”
Section: Risk Factors Of Aaasupporting
confidence: 85%
“…Calcification,109,110 and thrombus volumes,72 have been assessed in research settings with excellent reproducibility. In a study involving 75 patients, accurate assessment of thrombus volume using CTA was evidenced by low intra- (Pearson correlation coefficient 0.9974 (P<0.001), mean coefficient of variation 2.9%), and inter-observer (Pearson correlation coefficient 0.9983 (P<0.001), mean coefficient of variation 4.3%) variation 72. However, assessment is hindered by difficulty in delineation of surrounding anatomy and thrombus and high time requirements.…”
Section: Current Diagnosis Of Aaamentioning
confidence: 99%
“…Intraluminal thrombus is a feature of most AAAs and is correlated with the size of the aneurysm [67]. Thrombus has been suggested to be important in AAA pathogenesis by releasing proteolytic enzymes and proinflammatory cytokines from inflammatory cells trapped within fibrin [68].…”
Section: Aortic Thrombus and Antithrombotic Therapiesmentioning
confidence: 99%